MINING POSTS AND COMMENTS FROM ONLINE SOCIAL NETWORKS - JongoniSrikant, Dr. Prasadu Peddi, Dr. M. Laxmaiah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The comment thread as well as article extraction from newspaper's web pages are performed by Python scripts. One script will extract the newspaper article as well as another script that extracts comments related with the story. A comprehensive outline of the steps to be followed during the extraction process is provided. Newspaper websites are dynamic websites in that they collect content from multiple sources. They employ scripts that carry out functions like database information articles, comments on articles hyperlinks to other news sites, links to different news categories or topics as well as. They also populate the page with information from various sources now of visualization. The extraction of posts and comment threads of Web social media (YouTube as well as Facebook) is accomplished with two free online tools. An in-depth description of the steps to follow during the extraction process is presented in this paper.